The Crescendo Reaction in Patch Testing: A Key Diagnostic Sign in Allergic Contact Cheilitis from Modern Matte Lipsticks - Rahmat Firdaus Dwi Utama; Harijono Kariosentono; Ayu Kusuma Dewi; Shelly Lavenia Sambodo; Stella Gracia Octarica; Sugih Primas Adjie (Open Access Indonesian Journal of Medical Reviews, 2025)
Allergic contact cheilitis (ACC) from lipsticks is a frequent diagnostic challenge, often mimicking irritant contact cheilitis (ICC). The patch test is the diagnostic standard, but its accuracy relies heavily on the interpretation of reaction dynamics over time. This report illustrates the pivotal role of the crescendo reaction pattern in confirming an allergic etiology. A 21-year-old female presented with a six-month history of debilitating pruritus, papules, and subsequent xerosis with severe post-inflammatory hyperpigmentation on her lips. The symptoms were directly correlated with the daily use of several popular commercial matte and long-lasting lipsticks. Patch testing was performed with the European Standard Series and the patient’s own cosmetic products. While standard allergens were negative, three specific lipsticks elicited a classic crescendo reaction: a weak positive (+) erythema at 48 hours that intensified to a strong positive (++) reaction with papules and palpable infiltration at the 72- and 96-hour readings. This dynamic confirmed a Type IV hypersensitivity reaction and a diagnosis of ACC. Management focused on strict allergen avoidance and barrier repair, resulting in complete resolution of symptoms and significant improvement in her quality of life. In conclusion, the crescendo pattern observed in patch testing is a compelling in vivo marker of an allergic, memory T-cell-driven immune response. Its presence provides conclusive evidence for ACC, reliably distinguishing it from the decrescendo pattern characteristic of irritation. Meticulous observation of the temporal evolution of patch test reactions is paramount for accurate diagnosis and effective patient management in cheilitis.